The Effect of ICT-Based Learning on Student Motivation and Learning Outcomes in Economics Learning at SMAN 1 Sreseh - Agus Wahyudi; Sucipto Sucipto; Victor Maruli Tua L. Tobing (International Forum of Researchers and Lecturers, 2025)
This study explores the influence of Information and Communication Technology (ICT)-based learning media on student motivation and learning outcomes in economics subjects at SMAN 1 Sreseh. The quasi-experimental method was used to compare the effectiveness of ICT-based learning with conventional methods in grade X students. Data analysis also indicates a significant relationship between motivation levels and student learning outcomes. The study concludes that the integration of ICT in economic learning can improve student engagement, learning effectiveness, and their academic achievement, especially when supported by adequate infrastructure and training..